Optical-electronic sensor of spacecraft heat protection ablation - Hornostaev, G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Block diagram and results of tests on gas-dynamic stands are represented to
illustrate operation of the continuous ablation sensor, in which color light guides with a
diameter of 1 mm are used. It is shown that the application of compensating light filter in
the colorless channel makes it possible to create the meter invariant to external radiant
fluxes applied to the heat protection covering surface.